The Influence of Blood Sample Volume to the Growth of Microorganism in Blood Culture - Osman Sianipar Osman Sianipar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: One of the important things in infectious diseases management is bacterial detection. Bacterial finding is influenced by many factors and the most important thing is blood sample volume inoculated into culture bottles. Sometimes difficulty occurs whenever blood sample volume taken is not sufficient as recommended, especially in children.Objectives: The objective of this study is to investigate the influence of blood sample volume on microorganism growth in blood culture.Methods: A prospective observational study was taken to investigate the influence of blood sample volume on microorganism growth in blood culture from clinical specimen. The inclusion criteria were patients with infection, sepsis, invasive procedures and possible immunocompromized conditions. Blood sample volume was measured by the difference between the final volume and volume of medium, and expressed as sample/medium ratio. The Chi-Square and Fisher's exact tests were used to examine the proportion between inappropriate and appropriate sample/medium ratio.Results: There were 113 (30.4%) out of 372 culture bottles showed bacterial growth with 118 isolates. The gram-negative bacilli isolates were mostly found (67.8%). The proportion of bacterial growth in inappropriate recommended ratio was significantly higher comparing to the appropriate one. The different methods in detecting the bacterial growth did not influence the detection rate. The day-to-daY proportion of bacterial growth rate did not differ significantly.Conclusion: The sample/medium ratio seems do not influence the bacterial growth rate.Key words: blood sample volume - sample medium ratio - bacterial growth - blood culture